Coupling of Gain Medium and Extraordinary Optical Transmission for Effective Loss Compensation - Kaikun Niu; Zhixiang Huang; Ming Fang; Minquan Li; Xuanhua Li; Xianliang Wu (IEEE Access, 2018)
Gain mediums attract much attention due to their excellent amplification characteristics. However, the potential applications of gain mediums are severely limited because of the requirement of a high external energy to excite the media, thereby compensating for the ohmic loss. In this paper, we developed a theoretical model by numerically solving the coupled Maxwell's equations and semiclassical electronic rate equations using the finite-difference time-domain method. In the model, the active gain medium is represented by a four-level atomic system, and the atoms are pumped with a homogeneous pumping rate. Then, we investigated the loss compensation with the synergetic effects of gain mediums and extraordinary optical transmission (EOT) phenomena caused by the excitation of the surface plasmon polariton. With the proposal of a novel gain/metal/gain structure that is patterned to be a periodic subwavelength hole array, the self-consistent process of EOT phenomena coupled to the gain medium enables full compensation of the ohmic loss under a much lower pumping rate. This paper not only presents a novel structure but also provides deep insight into the interaction between nanostructures and gain mediums.